Differences in Ethical Judgment Based on the Presence or Absence of Buddhist Altars: An Application of the Bennett Method - Kosei TOGASHI; Nobumichi WATAHIKI; Luiza GATAN; Takatomo ITOI; Cristian VLAD (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This research analyses ethical judgement processes in Japanese organisations, in relation with the presence or the absence of Buddhist altars within the premises of the firm. While seeking to illustrate the impact of collectivism on organizational behaviour, this research sheds light on culture and the concept of shame in Japanese society, connecting this to the collective nature of people working in Japanese companies and how this specific behaviour evolved into competitive advantage over the years. Nevertheless, in regard to the focal points of employee interest, this research indicated that there was no evidence of collectivism, as it is usually described by Japanese business managers. The findings highlight important and intriguing issues for future research and scientific consideration.